French-speaking students’ academic experiences at a private provider of higher education offering foundation programmes - Gumbo, Mishack T (South African Journal of Higher Education, 2018)
Academic experiences of French-speaking immigrant students involve a negotiation of French language with the language of learning and teaching (LoLT). Utilising Legitimate Peripheral Participation (LPP), case study, observation, document analysis and a narrative inquiry, this research set out to explore the academic experiences of French-speaking students at a private provider of higher education offering foundation programmes as a route to mainstream degree programmes. It was found that sociocultural factors played vital roles in the survival of French-speaking students at the academic institution. South African students spoke Sotho and Zulu both within and outside of the lecture rooms, a scenario which undermined the capacity of French-speaking students’ to adapt academically and socioculturally to the academic institution. Unfriendliness on the part of South African students and introversion (an inherent character trait) as along with the incongruous posture of the French-speaking students in terms of their incessant use of the French language challenged their academic survival.